2021
DOI: 10.37763/wr.1336-4561/66.3.365378
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Features of the Oil-Heat Treated Woods From Tropical Fast Growing Wood Species

Abstract: This study aimed to evaluate the effect of oil-heat treatment on the anatomical, physical, and chemical properties of the tropical fast-growing wood species as gmelina (Gmelinaarborea) and mindi (Melia azedarach) wood. Vessel lumen area and diameter in radial and tangential direction of both species increased with increasing temperature. The fiber lumen areas in both woods were remarkably decreased by oil-heat treatment, and the fiber wall area increased considerably with increasing temperature. Both woods ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This is probably due to the use of palm oil. The fine band of high intensity observed around wavelength 1740 cm −1 of the wood samples treated with palm oil reflects the modification in carbohydrates (in hemicelluloses) by oxidation, of the content of C=O bonds of carboxylic acids due to palm oil [ 48 , 52 , 53 ]. The band at 1505 cm −1 , which highlights the vibrational stretching of aromatic skeletal C=C in lignin, is more accentuated for palm oil heat treatment, implying that this treatment degrades the wood lignin more than air heat treatment.…”
Section: Resultsmentioning
confidence: 99%
“…This is probably due to the use of palm oil. The fine band of high intensity observed around wavelength 1740 cm −1 of the wood samples treated with palm oil reflects the modification in carbohydrates (in hemicelluloses) by oxidation, of the content of C=O bonds of carboxylic acids due to palm oil [ 48 , 52 , 53 ]. The band at 1505 cm −1 , which highlights the vibrational stretching of aromatic skeletal C=C in lignin, is more accentuated for palm oil heat treatment, implying that this treatment degrades the wood lignin more than air heat treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies on the effect of OHT on improving wood properties have been reported by previous researchers (Bazyar, 2012;Dubey et al, 2011;Suri et al, 2021a;Suri et al, 2022;Wang & Cooper, 2005). Oil absorption contributes to increased dimensional stability, hydrophobicity, and resistance to mold and fungi (Dubey et al, 2011;Wang & Cooper, 2005).…”
Section: Introductionmentioning
confidence: 92%
“…Wood species in Indonesia that significantly increased in production are primarily fast-growing trees, like mindi (Melia azedarach), mangium (Acacia mangium), and sengon (Falcataria moluccana) (Febrianto et al, 2010;Haryanto et al, 2021;Rafly et al, 2022). Fast-growing wood species have the advantages of short growth rotation and short time for harvesting, but they have several disadvantages in terms of wood quality, such as lower density and shorter fiber than slow-growing wood species (Aisyah et al, 2021;Suri et al, 2021a;Yunita et al, 2022). Therefore, efforts to improve fast-growing wood quality through modification are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These three wood species belong to fast-growing species. Fast-growing wood species have the characteristics of small diameter, low quality, and contain many juvenile woods, resulting in low wood yield (Cahyono et al 2017;Suri et al 2021). Afrika wood has a specific gravity of 0.37 (Kim et al 2012(Kim et al , 2014), strength class of IV (Karlinasari et al 2021), and durability class of IV (Febrianto et al 2015).…”
Section: Introductionmentioning
confidence: 99%